The effect of anthropometry, eye - hand coordination and concentration on petanque pointing skills - Imelda Setiawan Sihotang; Ramdan Pelana; Sri Nuraini (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study was to determine the direct and indirect effects of anthropometry, eye hand coordination and concentration on petanque pointing skills. The research method is quantitative associative, with the test and non-test techniques, while the analysis technique used path analysis. The data is tested by using a distribution list and histogram. Central measures include the mean, median and mode. The spread indicators include variance and standard deviation, regression estimation error testing using the Liliefors technique and variance homogeneity testing using the Barlett test technique. The subject in this study were 50 athletes in North Sumatra with saturated sampling technique. The results of the assessment obtained anthropometric significant value for concentration with a significant value in (0.280), eye coordination - hand to concentration in (0.373), anthropometry to pointing skills in (0.013), eye coordination-hand to pointing skills in (0.443), concentration to pointing skills in (0.000).